A systematic review and meta-analysis of the in vivo haemodynamic effects of Δ9-Tetrahydrocannabinol - Sultan, Salahaden R.; Millar, Sophie A.; O’Sullivan, Saoirse E.; England, Timothy J. (MDPI, 2018)
∆9-Tetrahydrocannabinol (THC) has complex effects on the cardiovascular system. We aimed to systematically review studies of THC and haemodynamic alterations. PubMed, Medline, and EMBASE were searched for relevant studies. Changes in blood pressure (BP), heart rate (HR), and blood flow (BF) were analysed using the Cochrane Review Manager Software. Thirty-one studies met the eligibility criteria. Fourteen publications assessed BP (number, n = 541), 22 HR (n = 567), and 3 BF (n = 45). Acute THC dosing reduced BP and HR in anaesthetised animals (BP, mean difference (MD) −19.7 mmHg, p < 0.00001; HR, MD −53.49 bpm, p < 0.00001), conscious animals (BP, MD −12.3 mmHg, p = 0.0007; HR, MD −30.05 bpm, p < 0.00001), and animal models of stress or hypertension (BP, MD −61.37 mmHg, p = 0.03) and increased cerebral BF in murine stroke models (MD 32.35%, p < 0.00001). Chronic dosing increased BF in large arteries in anaesthetised animals (MD 21.95 mL/min, p = 0.05) and reduced BP in models of stress or hypertension (MD −22.09 mmHg, p < 0.00001). In humans, acute administration increased HR (MD 8.16 bpm, p < 0.00001). THC acts differently according to species and experimental conditions, causing bradycardia, hypotension and increased BF in animals; and causing increased HR in humans. Data is limited, and further studies assessing THC-induced haemodynamic changes in humans should be considered.